Gratitude in the Qur'an, A Thematic Qur'anic Study with a Grounded Theory Approach - Nadia Nurpadilah; Annida Nazirah; Muhammad Alif (International Forum of Researchers and Lecturers, 2025)
This study aims to comprehensively examine the concept of gratitude (shukr) from the perspective of the Qur'an by employing a thematic interpretation approach ( tafsīr al-maw ḍ ū'ī ) combined with the grounded theory method. This dual approach allows for an in-depth exploration of Qur'anic verses related to gratitude while also constructing theoretical frameworks derived directly from the primary data—namely, the Qur'anic text itself. The research adopts a qualitative, library-based methodology, where relevant verses are collected, categorized, and regularly analyzed to understand how gratitude is depicted, what forms it takes, and how it influences human life. The findings reveal that gratitude in the Qur'an goes beyond verbal expressions of gratitude to God. It encompasses inner awareness, acknowledgment of divine favor, wise utilization of blessings, and concrete actions that reflect obedience to God. Gratitude is presented as an active response to divine grace, resulting in positive behavior, spiritual closeness, and the strengthening of ethical and social dimensions in a believer's life. Moreover, the Qur'an affirms that those who are grateful are not only spiritually elevated but also promised an increase in blessings and a noble status in the sight of God. In the current socio-religious context, the value of gratitude holds significant relevance as a foundation for character development and emotional resilience. This study affirms that gratitude is a universal Islamic value that integrates theological, psychological, and ethical aspects. Thus, it is expected that this research contributes both theoretically and practically to the development of thematic Qur'anic studies and a deeper understanding of spiritual consciousness.